Inovasi Pelayanan Pajak Hotel Dan Hiburan Berbasis Online Di Badan Pendapatan Daerah Kota Makassar - Agus, Agus; Ansari, Isa; Nasrulhaq, Nasrulhaq (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2021)
ABSTRACTThe purpose of this study was to find out how the Online-Based Hotel and Entertainment Tax Service Innovation at the Makassar City Regional Revenue Agency. This study used qualitative description research methods and data collection techniques used  interviews, observation and documentation. The results of the study showed that online-based hotel and entertainment tax service innovations at the Makassar City Regional Revenue Agency were part of eleven types of taxes that  incorporated in the "SIMPAKDU" integrated tax information system. It provided a data recording device that directly supervised by Korsupgah KPK RI so that it could provide many benefits and made it easier for taxpayers because they no longer needed to come to the office for reporting, calculating and paying taxes. However, there were still types of taxes and taxpayers who still used the manual system and not all of them could  be reached to be online because of the high cost of the tools and the lacked of fulfillment of the tools caused by the lacked of budget. Keywords: Service innovation, Hotel and Entertainment Tax, Online Based